Decentralised control for reactive power sharing using adaptive virtual impedance. Issue 5 (16th January 2018) - Hu, Yalong; Xiang, Ji; Peng, Yonggang; Yang, Pengcheng; Wei, Wei
Abstract : The droop control strategy has been widely used in the microgrid. Though the real power sharing is accurate, the performance of reactive power sharing is not good due to the lack of global information. A new control strategy that employs an adaptive virtual impedance is proposed to improve the reactive power sharing accuracy without communication. In the proposed controller, reactive power sharing is realised through the adaptive virtual impedance, whose coefficient is set to the square of the reactive power sharing ratio. Only inductive virtual impedance is adopted by using the absolute value of the reactive power. The proposed controller only uses local information. Its reactive power sharing accuracy and the virtual impedance design principle are analysed and explained. Small signal stability of an inverter equipped with the proposed controller is analysed. It has been shown that the reactive power sharing error of the proposed controller could be reduced by less about 50% compared to conventional droop control. Real‐time simulation results are submitted to verify the effectiveness.